Penetrating ocular injury due to fish hook accident: A case report - Nyoman Tarita Dewi; Putu Rima Adilitha Widyasari; Fazella Kirara Sakti; Ida Ayu Putri Kartiningsih (DiscoverSys Inc., 2022)
Introduction: Open globe trauma is caused by sharp objects (lacerations) or blunt objects (ruptures). Lacerations can be divided into three parts: penetrating wound, intraocular foreign body (IOFB), and perforating wounds. One of the ocular laceration trauma that needs to be aware of is the penetration of fishing hooks. There are two important aspects of injuries due to fishing hooks: intraocular foreign bodies and infections.Case description: The patient of a 4-year-old girl with a chief complaint left eye was exposed to a fishing hook approximately 3 hours before coming to the hospital. Ophthalmological examination was obtained visual acuity on the right eye fixes and follow the object. Examination of the anterior segment of the right eye was found corneal edema, penetrating injury due to fish hook direction at nine o'clock. The fish hook was stick on the entire thickness of the cornea. Then we also found iris trauma and opacity in the lens. The patient was diagnosed with traumatic cataracts with ocular iridolysis dextra. Initial therapy is tobroson eye drop 1 drop every 3 hours, cefadroxil syrup three times a day, and methylprednisolone 3x1/2 tablets. The patient was advised to undergo surgery.Conclusion: Initial management should be quick and careful to aggravate the trauma. Adequate eye protection and supervision are necessary to prevent fishing hook trauma, especially children.